Sterile osteomyelitis: a cardinal sign of autoinflammation - Tiago Borges; João Santos; Sérgio Silva (Rheumatology)
Autoinflammatory bone disorders (ABDs) are characterized by sterile bone inflammation stemming from dysregulated innate immune responses. This review focuses on the occurrence of sterile osteomyelitis in ABDs and related diseases, notably chronic nonbacterial osteomyelitis (CNO) and its sporadic and monogenic forms, such as deficiency of the interleukin-1 (IL-1) receptor antagonist, Majeed syndrome, CNO related to FBLIM1 mutation, and pyogenic arthritis, pyoderma gangrenosum, and acne (PAPA syndrome). Additionally, other autoinflammatory disorders (AIDs) are discussed, including classical periodic fever syndromes (e.g., familial Mediterranean fever, cryopyrin- associated periodic syndromes), monogenic rare AIDs (such as hyperostosis-hyperphosphatemia syndrome, H syndrome, interferonopathies, and Singleton-Merten’s syndrome), polygenic AIDs with bone involvement (e.g., Schnitzler’s syndrome, systemic juvenile idiopathic arthritis, adult-onset Still’s disease, and calcium pyrophosphate deposition disease), and bone dysplastic syndromes. Sterile osteomyelitis emerges as a cardinal sign of autoinflammation, aiding clinicians in both diagnosis and management of ABDs. Treatment typically involves tumor necrosis factor inhibitors or IL-1 antagonists.